Annual Report to the Nation on the Status of Cancer, Featuring Cancer in Men and Women Age 20–49 Years. (30th May 2019) - Ward, Elizabeth M; Sherman, Recinda L; Henley, S Jane; Jemal, Ahmedin; Siegel, David A; Feuer, Eric J; Firth, Albert U; Kohler, Betsy A; Scott, Susan; Ma, Jiemin; Anderson, Robert N; Benard, Vicki; et al.
Abstract: Background: The American Cancer Society, Centers for Disease Control and Prevention, National Cancer Institute, and North American Association of Central Cancer Registries provide annual updates on cancer occurrence and trends by cancer type, sex, race, ethnicity, and age in the United States. This year's report highlights the cancer burden among men and women age 20–49 years. Methods: Incidence data for the years 1999 to 2015 from the Centers for Disease Control and Prevention- and National Cancer Institute–funded population-based cancer registry programs compiled by the North American Association of Central Cancer Registries and death data for the years 1999 to 2016 from the National Vital Statistics System were used. Trends in age-standardized incidence and death rates, estimated by joinpoint, were expressed as average annual percent change. Results: Overall cancer incidence rates (per 100 000) for all ages during 2011–2015 were 494.3 among male patients and 420.5 among female patients; during the same time period, incidence rates decreased 2.1% (95% confidence interval [CI] = −2.6% to −1.6%) per year in men and were stable in females. Overall cancer death rates (per 100 000) for all ages during 2012–2016 were 193.1 among male patients and 137.7 among female patients. During 2012–2016, overall cancer death rates for all ages decreased 1.8% (95% CI = −1.8% to −1.8%) per year in male patients and 1.4% (95% CI = −1.4% to −1.4%) per year in females. Important changes in trends were stabilization of thyroid cancer incidence rates in women and rapid declines in death rates for melanoma of the skin (both sexes). Among adults age 20–49 years, overall cancer incidence rates were substantially lower among men (115.3 per 100 000) than among women (203.3 per 100 000); cancers with the highest incidence rates (per 100 000) among men were colon and rectum (13.1), testis (10.7), and melanoma of the skin (9.8), and among women were breast (73.2), thyroid (28.4), and melanoma of the skin (14.1). During 2011 to 2015, the incidence of all invasive cancers combined among adults age 20–49 years decreased −0.7% (95% CI = −1.0% to −0.4%) among men and increased among women (1.3%, 95% CI = 0.7% to 1.9%). The death rate for (per 100 000) adults age 20–49 years for all cancer sites combined during 2012 to 2016 was 22.8 among men and 27.1 among women; during the same time period, death rates decreased 2.3% (95% CI = −2.4% to −2.2%) per year among men and 1.7% (95% CI = −1.8% to −1.6%) per year among women. Conclusions: Among people of all ages and ages 20–49 years, favorable as well as unfavorable trends in site-specific cancer incidence were observed, whereas trends in death rates were generally favorable. Characterizing the cancer burden may inform research and cancer-control efforts.